The Affordance Theory and the Pedagogical Affordances - Al-Ibrahim, Amal Abdullah (Journal of Educational and Psychological Sciences, 2021)
The current era is witnessing a global revolution in information and communication technology, and education is one of the fields that affected and affected by technologies. While educational practitioners have been using modern technologies to support the learning and teaching process. The Affordances theory is considered one of the useful and effective theories to innovate technologies in education. So this paper aims to introduce a deep definition of this theory, also it compares Affordances concept by the two most important scholars in the field (Gibson and Norman). The paper will present the concept of this theory from their point of view and present a definition of the theory. Finally, some previous studies on the pedagogical affordances for a number of modern technologies will be presented and reviewed. * في هذا البحث أقدم للقارئ ملخصا لبحث عن نظرية إمكانيات الفعل. وهو جزء من رسالة الدكتوراه المقدمة لجامعة اكستر، المملكة المتحدة. الباحثة